2003
DOI: 10.1039/b303745b
|View full text |Cite
|
Sign up to set email alerts
|

Can an in silico drug-target search method be used to probe potential mechanisms of medicinal plant ingredients?

Abstract: Medicinal plants have been explored therapeutically in traditional medicines and are a valuable source for drug discovery. Insufficient knowledge about the molecular mechanism of these medicinal plants limits the scope of their application and hinders the effort to design new drugs using the therapeutic principles of herbal medicines. This problem can be partially alleviated if efficient methods for rapid identification of protein targets of herbal ingredients can be introduced. Efforts have been directed at d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 130 publications
0
46
0
2
Order By: Relevance
“…The in silico method for identifying their molecular targets is INVDOCK (Chen and Zhi, 2001;Chen and Ung, 2002;Chen et al, 2003), which conducts an automated search of every human and mammalian protein entry in the protein 3D structure database, Protein Data Bank (PDB) (Berman et al, 2000) to identify proteins to which each of these TCM herbal ingredient can bind. INVDOCK is based on a ligand-protein inverse docking strategy such that a compound is docked to known ligand-binding pockets of each of the protein entries in the PDB database.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The in silico method for identifying their molecular targets is INVDOCK (Chen and Zhi, 2001;Chen and Ung, 2002;Chen et al, 2003), which conducts an automated search of every human and mammalian protein entry in the protein 3D structure database, Protein Data Bank (PDB) (Berman et al, 2000) to identify proteins to which each of these TCM herbal ingredient can bind. INVDOCK is based on a ligand-protein inverse docking strategy such that a compound is docked to known ligand-binding pockets of each of the protein entries in the PDB database.…”
Section: Data Collectionmentioning
confidence: 99%
“…Because of a growing interest in therapeutic agents based on TCM, increasing effort has been directed towards scientific proof, clinical evaluation and molecular analysis of TCM (Tang and Eisenbrand, 1992;Chan, 1995;Cheng, 2000;Yuan and Lin, 2000;Chen and Ung, 2001; Chen et al, 2003). A Medline survey in 2001 (Wheeler et al, 2003) showed that there are 6504 Chinese herb-related articles published in 662 journals in the period of 1966(Pach et al, 2002.…”
Section: Introductionmentioning
confidence: 99%
“…该策略以小分子化合物为探针, 在已知结 构的数据库内搜寻可能与之结合的蛋白, 通过研究小分 子和已知结构的靶点蛋白之间的相互作用, 预测药物潜 在的作用靶点 [108] . 作为一种补充策略, 反向分子对接 已经成为确定小分子化合物潜在靶标的有效工具之一.…”
Section: 化学生物信息学预测unclassified
“…Therefore, DCDB will be updated twice a year, including one minor update for data only, and one major update with possible changes in database schema and potential integration of new analysis tools. The next major update has been projected to launch an integrated pathways analyzer for mining drug target connections, and a software tool to identify potential 'off-targets' for drugs, based on our inversedocking strategy (Chen et al, 2003). These tools are expected to offer extra power and utility when molecular mechanisms of beneficial drug interactions are analyzed.…”
Section: Summary and Future Prospectivesmentioning
confidence: 99%